strategy of invention and innovation in products design - Abdul Khaleq Samin Fattah (الاكاديمي)
The problem of the study intiteld (Strategy of invention and innovation in products design) was present of how can the strategy of invention & innovation contribute in effect way products design , research importance lies to identify of most important strategies which followed by industries to meet needs & wishes of the consumers in superiority & success, the aim ot the research is to piano the effect limit ot invention & innovation strategy possibility to subtract new products to the markets and insertion the research importance to the invention, innovation and competition areas, the research limits included products users differ their segments, cultures and physical potential.